A közszféra bérszintje és a magánszektorból átlépők szelekciója 1997-2008-ban - János Köllő (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
– The paper looks at the effect of exceptionally large fluctuations in the level of public sector pay on the number and quality of workers moving from the private to the public sector in Hungary. Special emphasis is put on the unique pay rises taking place before and after the 2002 elections. The study is based on a large panel of administrative data covering 1997-2008. The data suggest that flows to the public sector fell during and after the wage hikes. Repeated cross-section and panel wage regressions suggest that the quality of entrants, measured with their residual wages achieved in the private sector prior to their departure, temporarily improved. A one per cent increase in the expected public sector pay increased the mean residual private-sector wage of those leaving for the public sector by more than half per cent. This selection effect was significantly stronger in the case of young workers. However, the decline of inward mobility substantially reduced the potentially benign impact of positive selection on the total workforce of the public sector.
Keywords: J45; J62; 330; public sector; wages; mobility; Vergütungssystem im öffentlichen Dienst; Arbeitsmobilität; Privatwirtschaft; Öffentlicher Dienst; Ungarn